Lipocalin-Type Prostaglandin D Synthase Scavenges Biliverdin in the Cerebrospinal Fluid of Patients with Aneurysmal Subarachnoid Hemorrhage. Issue 9 (September 2014) - Inui, Takashi; Mase, Mitsuhito; Shirota, Ryoko; Nagashima, Mariko; Okada, Tetsuya; Urade, Yoshihiro
Lipocalin-type prostaglandin (PG) D synthase (L-PGDS) is the second major protein in human cerebrospinal fluid (CSF) and belongs to the lipocalin superfamily composed of various secretory lipophilic ligand transporter proteins. However, the endogenous ligand of L-PGDS has not yet been elucidated. In this study, we purified L-PGDS from the CSF of aneurysmal subarachnoid hemorrhage (SAH) patients. Lipocalin-type PG D synthase showed absorbance spectra with major peaks at 280 and 392 nm and a minor peak at around 660 nm. The absorbance at 392 nm of L-PGDS increased from 1 to 9 days and almost disappeared at 2 months after SAH, whereas the L-PGDS activity decreased from 1 to 7 days and recovered to normal at 2 months after SAH. These results indicate that some chromophore had accumulated in the CSF after SAH and bound to L-PGDS, thus inactivating it. Matrix assisted laser desorption ionization time-of-flight mass spectrometry of L-PGDS after digestion of it with endoproteinase Lys-C revealed that L-PGDS had covalently bound biliverdin, a by-product of heme breakdown. These results suggest that L-PGDS acted as a scavenger of biliverdin, which is a molecule not found in normal CSF. This is the first report of identification of a pathophysiologically important endogenous ligand for this lipocalin superfamily protein in humans.